Introduction of Complementary Foods and Inadequate Dietary Habits in Infants Under 12 Months of Age in Three Regions of Brazil. (29th May 2020) - Campos, Vanessa; Anater, Andrea; Hampton, Joel; Eldridge, Alison
Abstract: Objectives: The objective of this study was to describe the dietary patterns of Brazilian infants from birth to 12 mo of age and to assess their adherence to feeding guidelines. Methods: A cross-sectional random sample of infants aged 0–11.9 mo (n = 216) was identified in three census regions of Brazil (Northeast, Southeast, and South). In-person interviewers asked caregivers about breastfeeding practices and duration and timing of introduction of solid foods. Prevalence was estimated for specific age groups. Results were weighted to be representative of the infant population in Brazil. Results: Almost 80% of the infants below 6 mo of age were ever breastfed. The percentage of infants that were currently breastfeeding decreased from birth through the age of 12 mo. Breastfeeding rates (i.e., currently breastfeeding) were 76.9% for infants 0–2.9 mo, 70.4% for those 3–5.9 mo and 50.5% for infants 6–11.9 mo. Early introduction of complementary foods was identified. Cow's milk was consumed by 12.4% of infants consumed cow's milk at 4–5.9 mo, and 51.6% were receiving cow's milk at 6–11.9 mo. Approximately 25% of 4–5.9 mo olds were consuming juice, and by 6–11.9 mo, 79.2% were consuming juice. On the other hand, 47.5% of 6–11.9 mo olds were consuming iron-fortified infant cereal and 70.8% were consuming meat. Conclusions: We identified some feeding practices during early infancy among Brazilian infants that do not meet governmental recommendations. These include early introduction of cow's milk and consumption of fruit juices before one year of age. Funding Sources: Supported by Nestle Research, Lausanne Switzerland.